Inappropriate hospital admission as a risk factor for the subsequent development of adverse events: a cross-sectional study - San José Saras, Diego; Vicente-Guijarro, Jorge; Sousa, Paulo; Moreno-Nuñez, Paloma; Aranaz Andrés, Jesús María (BMC Medicine, 2024)
Background: All health overuse implies an unnecessary risk of patients suffering adverse events (AEs). However, this hypothesis has not been corroborated by direct estimates for inappropriate hospital admission (IHA). The objectives of the study were the following: (1) to analyze the association between IHA and the development of subsequent AEs; (2) to explore the distinct clinical and economic implications of AEs subsequent IHA compared to appropriate admissions. Methods: An observational cross-sectional study was conducted on hospitalized patients in May 2019 in a high-complexity hospital in Madrid, Spain. The Appropriateness Evaluation Protocol was used to measure IHA, and the methodologies of the Harvard Medical Practice Study and the European Point Prevalence Survey of Healthcare-associated Infections were used to detect and characterize AEs. The association between IHA and the subsequent. Results: A total of 558 patients in the hospital ward were studied. IHA increased the risk of subsequent occurrence of AEs (OR [95% CI]: 3.54 [1.87 to 6.69], versus appropriate) and doubled the mean AEs per patient (coefficient [95% CI]: 0.19 [0.08 to 0.30] increase, versus appropriate) after adjusting for confounders. IHA was a predictive variable of subsequent AEs and the number of AEs per patient. AEs developed after IHA were associated with scheduled admissions (78.9% of AEs, versus 27.9% after appropriate admissions; p < 0.001). Compared with AEs developed after appropriate admissions, AEs after IHA added 2.4 additional days of stay in the intensive care unit and incurred an extra cost of €166,324.9 for the studied sample. Conclusions: Patients with IHA have a higher risk of subsequent occurrence of AE. Due to the multifactorial nature of AEs, IHA is a possible contributing factor. AEs developed after IHA are associated with scheduled admissions, prolonged ICU stays, and resulted in significant cost overruns. © 2023, BioMed Central Ltd., part of Springer Nature.
Keywords: adverse events; appropriateness of health care; inappropriate hospital admission; patient safety; Scopus; JCR